2012
DOI: 10.3109/15412555.2011.648030
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease and SocioEconomic Status: a Systematic Review

Abstract: Social and economic disadvantage appears to have a significant consistent impact on COPD mortality and morbidity. These findings point to the need for public health strategies and research to address socioeconomic status disparity in individuals with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
132
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(155 citation statements)
references
References 24 publications
14
132
1
8
Order By: Relevance
“…A comprehensive review has found that there are increased risks relating to cardiovascular disease as well as access to invasive cardiac procedures [7,8], chronic kidney disease [9], diabetes mellitus [10] as well as in cancer survival [11]. There has been emerging data in various pulmonary diseases that alludes to a similar observation noted in other chronic diseases [12][13][14][15]. This review attempts to clearly outline the documented literature in regards of socioeconomic status and its relationship to common chronic respiratory diseases as well as highlight the role of SES is advanced lung disease as a barrier to access to health care.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A comprehensive review has found that there are increased risks relating to cardiovascular disease as well as access to invasive cardiac procedures [7,8], chronic kidney disease [9], diabetes mellitus [10] as well as in cancer survival [11]. There has been emerging data in various pulmonary diseases that alludes to a similar observation noted in other chronic diseases [12][13][14][15]. This review attempts to clearly outline the documented literature in regards of socioeconomic status and its relationship to common chronic respiratory diseases as well as highlight the role of SES is advanced lung disease as a barrier to access to health care.…”
Section: Introductionmentioning
confidence: 96%
“…Extensive research has been conducted to determine if SES affects the status and risk of developing COPD and www.journals.viamedica.pl Figure 1. Proposed relationship between socioeconomic status (SES) and healthcare delivery in the setting of chronic respiratory disease mortality [12]. Studies analyzing SES and COPD have been outlined in Table 2.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…La edad promedio fue: 65,5(±10,3) años y la distribución por género mostró la presencia de 24(54,5%) hombres. La mayoría de la población eran personas de estratos socioeconómicos 1 y 2, nivel de educación primaria incompleta y en el momento de la evaluación se encontraban en su hogar o desempleados (Ver Tabla 1 En relación al contexto socio-demográfico, llama la atención el bajo nivel de escolaridad de los pacientes, perteneciendo la mayoría al régimen subsidiado y todos a los estratos socioeconómicos 1 a 3; este factor tiene gran relevancia en EPOC [15][16][17] , se considera que los pacientes tienen mayor riesgo de desarrollar complicaciones al tener una mayor probabilidad de presentar un deficiente estado nutricional, hacinamiento, exposición a contaminantes, entre ellos el tabaquismo y la biomasa; desarrollo de infecciones respiratorias y dificultades en el acceso a la atención de la salud 4,15 .…”
Section: Resultsunclassified
“…ХОБЛ является одной из наиболее актуальных медико социальных проблем, обусловленной не только широкой распро страненностью заболевания, но и высоким риском серьезных осложнений, которые приводят к инва лидизации и смерти, в т. ч. трудоспособного населе ния [1][2][3]. Развитие обострений является характер ной чертой течения ХОБЛ [4][5].…”
Section: обзорыunclassified